A STUDY ON WORK FROM HOME AND WORK LIFE BALANCE OF IT SECTOR WOMEN EMPLOYEES REFERENCE TO PATHANAMTHITTA DISTRICT - Dr. Roni Jain Raju (Galaxy International Interdisciplinary Research Journal, 2021)
The novel corona virus (COVID-19) is a pandemic sweeping across the globe, has challenged society in ways once considered unimaginable, forcing people to reconsider a wide variety of practices, from work, to leisure, to basic travel and daily tasks. Today’s work environment and the culture have seen a sea change. The corona virus pandemic has dramatically altered the workplace. To slow the virus’s spread and protect employees, many companies have shifted to remote work, with video calls and instant messaging replacing meetings and break room conversations. Therefore, the study focuses on the work from home and maintenance of work life balance among women executives working in IT Parks.Sample Area selected for this study is Pathanamthitta District of Kerala state. The primary data is collected through structured questionnaire from 60 women employees in IT Parks. The study found that majority of the respondents is productive and satisfied with work from home arrangements during Covid times.